(3eNJUQ Shb GdQbjbs - (3eLghds; (3GHf fHGJI , eMeO Hf eMeO Hf eMeO Hf GdMSf GdLPGej GdaGQbj GdeUQj, LeGd GdOjf CHh HcQ,J (B768 (3g` s ((3eMeO Hf YHOGddg GdHQchj GdTGaYj s)
(3ChdgG (B:s
(3MeOkG ddg GdPj CTQb ef TehS eYGQag CfhGY GdeYGQa agPG GdJbGW OQQ hgh OjhGf XQja, eNJUQ dWja, eQJH Ydi MQha GdeYLe s
(3BNQgG (B:s
(3NJGegG hCQab HeVfGc aeG Shi GSeg hdG JZjQ eG Hbi ef QSeg hGdMeO ddg hMOg s
(3ddfGSN aj BNQ GdeNWhWI CHjGJ dg aj GdJgfFI hGdeOjMs
(3eQJH Ydi MQha GdeYLes
(3hHgG fXGe GdJYbjHIs
(3hGdfSNI HgG VHW s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdCOHs